Direct microstructure design by hot extrusion – High-temperature shape memory alloys with bamboo-like microstructure. (15th March 2019) - Niendorf, T.; Lauhoff, C.; Karsten, E.; Gerstein, G.; Liehr, A.; Krooß, P.; Maier, H.J.
Abstract: High-temperature shape memory alloys are promising candidates for actuation/damping applications at elevated temperatures. To account for pronounced instabilities at elevated temperatures of conventional alloys, novel alloy systems have been developed to address this issue. Yet, most systems suffer from high costs/limited formability. Bamboo-like microstructures have proven to provide for a suitable microstructural condition for superior performance in numerous alloys, however, robust processing of promising high-temperature shape memory alloys is challenging. The current study reports on a novel thermo-mechanical processing route allowing robust processing of hard to form Co-Ni-Ga shape memory alloys. This will assist to overcome a major roadblock towards widespread use of these materials. Graphical abstract: Unlabelled Image